Trans-Screens of Gender and Jewishness in Jill Soloway’s Transparent: Post-Network TV and the Screendance Scene - Schwadron, Hannah (The International Journal of Screendance, 2019)
This essay analyzes the artful insertion of screendance scenes in Season Two of Jill Soloway’s Amazon hit, Transparent (2014- ), highlighting how bodies and camera choreograph affective connections core to the plot in this televisual portrait of a Jewish American family. In doing so, I underscore a layered screenic trans-ness that conjoins circular manipulations of time and bodily action to overlay transgender and transhistorical experiences as co-constitutive themes.